Comparison of Electrical Properties of Ni/n‐GaN Schottky Diodes on c‐Plane and m‐Plane GaN Substrates. Issue 8 (13th November 2017) - Yamada, Hisashi; Chonan, Hiroshi; Takahashi, Tokio; Shimizu, Mitsuaki
Abstract : The electrical properties of un‐doped and lightly Si‐doped GaN grown on c‐ and m‐plane GaN substrates by metal organic chemical vapor deposition are investigated. The step‐flow growth modes are realized for c‐ and m‐plane GaN epitaxial layer. The carbon contamination in the c‐plane GaN and m‐plane GaN, grown at 1120 °C and V/III = 1000, are found to be 1.4 × 10 16  cm −3 and 5.0 × 10 15  cm −3, respectively. The m‐plane GaN follows a linear correlation between the carrier concentration and the Si atomic concentration. The Ni/n‐GaN (Si; 1 × 10 16  cm −3 ) Schottky vertical diodes on the c‐ and m‐plane GaN substrates reveal that the reverse current–voltage ( I–V ) curves are fitted by using the thermionic field emission model under the measured carrier concentration and the Schottky barrier height. The leakage current of the m‐plane GaN is three orders of magnitude larger than the c‐plane GaN, mostly due to the difference in the Schottky barrier height. Abstract : This work is focused on understanding the electrical properties of c‐ and m‐plane GaN epitaxial layers grown by metal organic chemical vapor deposition. Residual carbon, oxygen, and silicon atoms are effectively suppressed by using the off‐angle of the m‐plane GaN substrates, which demonstrates its potential applications in the field of power electronics.